ANALISIS KANDUNGAN MERKURI (Hg) PADA IKAN NILA (Oreochromis niloticus L.) BUDIDAYA KERAMBA DI SEKITAR WADUK RIAM KANAN KECAMATAN ARANIO - Aditya Rahman; Kresna Dinta Masmitra; Anni Nurliani (Universitas Sultan Ageng Tirtayasa, 2016)
ABSTRACTThis study aims to determine the content of heavy metals mercury contained in the fish Tilapia (Oreochromis niloticus L.) aquaculture cages around the Riam Kanan reservoir and compare it with quality standards based on the Decree of the Head of BPOM No. HK.00.06.1.52.4011 about the maximum limit of metal contamination in food, especially in fish. This study was conducted from September to December 2011. Sampling was conducted at three stations covering the village of Tiwingan Baru, Tiwingan Lama dan Aranio in the Aranio district. Sampling was done by purposive sampling method or sampling intentionally with certain considerations that are considered important. Mercury analysis performed using Atomic Absorption Spectrophotometer (AAS) instrument. Result showed that the average content of mercury in sediment samples at the first station of 0,0262 mg/kg; the second station of 0,1489 mg/kg and not detected at the third station, the content is still below the set threshold. The content of mercury in water samples of Riam Kanan reservoir at all stations are still below the threshold of water quality standards according to Government Regulation No. 82 of 2001. Result on the mercury content of Tilapia fish meat samples at all stations are still below the standards threshold based on the Decree of the Head of BPOM about the maximum limit of metal contamination in food, especially in fish.